2022
DOI: 10.1371/journal.pone.0263821
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug adherence in children in southern Ethiopia: A cross sectional study

Abstract: Background Epilepsy is one of the commonest chronic neurological disorders with serious health consequences. Treatment adherence is one of the determinants of seizure control. This study was designed to determine factors affecting antiepileptic drug adherence among children with epilepsy. Methods A cross sectional study was conducted on 192 children with epilepsy (≤14 years of age) on follow-up at a pediatric neurology clinic in Southern Ethiopia from January 1st to August 30th, 2019. Medication Adherence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
2
13
0
3
Order By: Relevance
“…18,19 Similarly poor family income affected adherence significantly in this present study. This finding is similar to finding by Dima et al 8 This could be due to the out-of-pocket payment done by most families in our setting and the high cost of the anti-epileptic drugs as parents or caregivers may not be able to sustain these drugs. Abebaw et al had reported that people living with epilepsy who paid for AEDs were more likely to have poor adherence compared to those who got theirs for free.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…18,19 Similarly poor family income affected adherence significantly in this present study. This finding is similar to finding by Dima et al 8 This could be due to the out-of-pocket payment done by most families in our setting and the high cost of the anti-epileptic drugs as parents or caregivers may not be able to sustain these drugs. Abebaw et al had reported that people living with epilepsy who paid for AEDs were more likely to have poor adherence compared to those who got theirs for free.…”
Section: Resultssupporting
confidence: 91%
“…Though, Dima and Shibeshi study population were children, they however made use of children who were 14 years and below whose parents may be responsible for administering the drug to them unlike this present study whose study population extended to children up to 18 years, and probably the older the patient the more likely they will take the drugs unsupervised. 8 Although Nazziwa et al by self-reporting had an adherence level as high as 79.5% among children this did not correspond to their serum AED levels as the latter was as low as 22.1%. 7 This further highlights the need for serum AEDs levels as relying on only self-reporting may not be reliable.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations